MENINGKATKAN LOGIKA MATEMATIKA DAN KERJASAMA MUATAN MATEMATIKA SISWA KELAS V SDN BAHALAYUNG KAB. BARITO KUALA - Ma'arif, Miftah Amrul; Noorhapizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problems encountered in this study were low mathematical logic abilities and cooperation skills among students. The main factors causing this were students' lack of understanding of the material, lack of participation, boredom during learning, and a tendency to rely on friends in group activities. To overcome these problems, the BALOGO model was applied. The objective of this study was to describe and analyze improvements in mathematical logic skills and collaboration skills. The study was conducted using a qualitative and quantitative approach in the form of Classroom Action Research over four sessions, with a sample consisting of 23 students, including 15 males and 8 females in Grade V at SDN Bahalayung Elementary School, Barito Kuala Regency. The data were presented in graphical form. The results showed a significant increase in mathematical logic intelligence from 13% to 96% with the criterion of “highly skilled,” and in cooperation skills from 30% to 91% with the criterion of “highly skilled.” The conclusion drawn from the learning process in mathematics using the BALOGO model is that it can enhance students' mathematical logic intelligence and cooperation skills.